2017
DOI: 10.1016/j.neuroscience.2016.11.045
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of freezing while turning in Parkinson’s disease

Abstract: Freezing of gait (FoG) in people with Parkinson’s disease (PD) is an environmentally sensitive, intermittent problem that occurs most often during turning. FoG is difficult for clinicians to evaluate and treat because it can be difficult to elicit during a clinical visit. Here, we aimedto develop a clinically valid objective measure of freezing severity during a 2-minute 360 degrees turning-in-place. Twenty-eight subjects with PD (16 freezers, FoG+, and 12 nonfreezers, FoG−) in the “off” state and 14 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
120
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 39 publications
5
120
1
1
Order By: Relevance
“…The sample sizes varied from 1 [28] to 48 PD [51] per study, with a non-PD group being included in a few studies [28, 40, 48, 51, 53, 56]. Disease severity, when reported, ranged from 2 to 4 according to the Hoehn and Yahr scale.…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes varied from 1 [28] to 48 PD [51] per study, with a non-PD group being included in a few studies [28, 40, 48, 51, 53, 56]. Disease severity, when reported, ranged from 2 to 4 according to the Hoehn and Yahr scale.…”
Section: Resultsmentioning
confidence: 99%
“…to provoke FOG. Stepping in place and rapid turning on the spot are both effective ways to provoke FOG [5][6][7][8]. However, these two tests have not been compared back to back.…”
mentioning
confidence: 99%
“…Two studies used the more stringent criterion of the NFOG‐Q > 3 to define a participant as a freezer . The results of one of these studies showed that none of the participants with a NFOG‐Q score < 3 experienced freezing during their FOG‐provoking protocol in the off medication state . The NFOG‐Q was not always administered by the same testers on both occasions, but protocols in both studies were rigorously standardized between testers and across centers in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 The results of one of these studies showed that none of the participants with a NFOG-Q score < 3 experienced freezing during their FOG-provoking protocol in the off medication state. 43 The NFOG-Q was not always administered by the same testers on both occasions, but protocols in both studies were rigorously standardized between testers and across centers in both studies. We also statistically checked whether the same tester scores and varying tester scorers showed more variability, but this was not the case.…”
Section: Discussionmentioning
confidence: 99%